قاعدة لا ضرر ولا ضرار وأثرها في فقه الأسرة "نماذج مختارة" - أوبیش, مسعودة (University of Eloued-جامعة الوادي, 2016)
This research titled: Base do no harm and its impact on the jurisprudence of the family "selected models", shows the extent to which the scientists to this rule, and the statement of its impact in the jurisprudence of the family. Contained this research on two chapters, Me first chapter theoretical study and that a statement on the concept of doctrinal base, then the definition of base do no harm, and resulted to be the rule of the major basic rules, agreed upon scholars, and are valid for a protest by; because the origin of modern NabaWi Sharif, the second chapter Fna statement on the impact of the base do no harm in the jurisprudence ofthe family; because it is the nucleus of the Muslim community, and by mentioning models in the period of the engagement and the other in the marriage, and the statement of the impact of this rule there. The research found that in the last damage paid in Islamic law, either before or after the fact, and show through selected models.
مذكرة ماستر
Keywords: قاعدة لاضررولاضرار/فقه الاسرة; The rule of harm / family jurisprudence